Expanding the Build Plate: Functional Morphing 3D Printed Structures Through Anisotropy - Loukaides, Evripides G. (Frontiers in Materials, 2020)
Certain types of patterned metamaterials - gridshells and honeycombs - are capable of bistable behaviour through a tailored combination of local and global geometric parameters. This is an alternative to prestressed or composite materials, which are typically used to induce multistability in thin structures. Globally bistable structures, contrary to arrays of bistable elements, allow large deformations in a single step. Furthermore, this category of structures offers greater manufacturability and scalability compared to laminate, prestressed or multimaterial shells, since only geometry has to be considered. The simplicity of the material and geometrical requirements afford the designer easy and direct embedding in larger functional structures. In this study, the local and global response of bistable gridshells is interrogated through a manageable strain energy model, as well as through numerical and experimental methods. In addition, construction of bistable gridshells by employing various additive methods is examined and prototypes are presented for a series of functional devices. Finally, the availability of printed parts much larger than the build plate using commercial 3D printers is demonstrated, effectively ``expanding'' the dimensions of the build plate.